Anuria and Hydronephrosis due to Ureteropelvic Junction Obstruction: A Case Report - Emami, Elham; Safari, Samane (Journal of Pediatric Nephrology, 2021)
A 3- year- old boy presented with abdominal pain and distension, lower extremities and facial edema, and anuria for several days that was associated with ureteropelvic junction obstruction (UPJO). Initial ultrasonography showed the presence of a massive bilateral hydronephrosis with UPJO and a computerized tomography (CT) scan without contrast revealed a massive hydronephrosis and hydroureter (grade 3). A follow-up study, after relief of ureteral obstruction, showed the reversal of this pattern. Blood biochemical tests revealed a severe acidosis, hyperkalemia, and a BUN/Cr ratio of more than 20. The patient underwent emergency nephrostomy. The general condition of the patient improved. Abdominal distention reduced, levels of urea and creatinine decreased, and acidosis resolved. A CT scan revealed an almost complete disappearance of the hydronephrosis and a normal ureter. Ureteropelvic junction obstruction (UPJO) was established as the cause of giant hydronephrosis.